Usulan Pemilihan Supplier Bahan Baku Join Break Road dengan Menggunakan Metode Analytical Network Process dan Metode Analytical Network Preference by Similarity to Ideal Solution : (Studi Kasus PT Ciptaunggul Karya Abadi) - Dimas Sugianto; Deny Wibisono; Puji Suharmanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Selection of suppliers is a critical aspect that requires serious attention from every company, as it not only impacts the improvement of the supply chain quality but also affects the quality of the products produced. The current issue faced by PT Ciptaunggul Karya Abadi in the supplier selection process involves conducting direct surveys to several suppliers and comparing prices, which results in delivery delays and subsequent production delays. This situation forces PT Ciptaunggul Karya Abadi to find alternative suppliers unexpectedly. This research employs the Analytical Network Process (ANP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods in the supplier selection process at PT Ciptaunggul Karya Abadi. The objective of this study is to combine the ANP and TOPSIS methods to enhance the accuracy of decision-making in supplier selection. The results of this research identified four criteria and 12 sub-criteria, and the prioritized ranking of the best suppliers for PT Ciptaunggul Karya Abadi shows that PT Baja Kencana Sakti ranks the highest with a preference value of 0.56693, followed by PT Stilmetindo Prima with a preference value of 0.44565, and PT Fujimaki Steel with a preference value of 0.39298.